(untitled) (Bangladesh Journal of Medical Microbiology, 2020)
The emergence of carbapenemase producing Escherichia coli, the first hospital and community-acquired opportunistic pathogen now become a great public health concern. A total of 23 clinical isolates of carbapenemase producing E. coli from extraintestinal infections in a tertiary care hospital of Bangladesh were studied. Highest percentage of carbapenemase producing E. coli isolates were from urine samples (52.2%) followed by 21.7% from each of wound swab and pus and 4.1 % from blood samples. Among the E. coli isolates 69.6% were from indoor patients and 30.4% were from outdoor patients. All the isolates (100%) were positive for NDM of which 13% were NDM and OXA-48 co-producers by conventional PCR. Carbapenemase producing E. coli isolates were resistant to most of the antibiotic tested except for nitrofurantoin, colistin, polymyxin B and tigecycline with a sensitivity of 66.7%, 82.6%, 95.7% and 100% respectively. Bangladesh J Med Microbiol 2020; 14 (1): 3-6